Comparison of Self-Tapping Screws Versus Erich’s Arch Bar Wiring for Occlusion Maintenance in the Surgical Management of Mandibular Fracture: A Randomized Control Trial - Begum, Shahida; Ahmed, Toufiqua; Hossain, Mohammad Azmal; Akhtar, Mst Mousumi; Akter, Mahmuda; Soma, Sharmin Aktar; Kamruzzaman, Mohammed (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Conventional methods like Erich’s arch bars and eyelet wires are currently most common methods for achieving temporary inter-maxillary fixation (IMF). Objectives: The purpose of the present study was to compare the efficacy of Self-tapping screws over Erich’s arch bar wiring for inter maxillary fixation in the treatment of mandibular fractures. Methodology: This was a randomized control trial study. Study duration was one year from October 2014 to September 2015. This study involved patients with mandibular fractures aged 22 to 65 years who visited Department of Oral & Maxillofacial Surgery at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. After random sampling according to inclusion and exclusion criteria surgical treatment was done by miniplate osteosynthesis. Study population were divided into two groups. In group A, temporary MMF was done with Erich’s arch bar and in group B treatment was given with self-tapping screws. The study outcomes were total time required for achieving temporary MMF, number of wire stick injury, stability of occlusion and oral hygiene index. All the parameters were measured preoperatively and postoperatively for 14 days up to removal of screws or arch bars. Results: The mean time taken for temporary MMF was 11.31±2.46 min with screws as compared to 84.72±14.30 min with Erich’s arch bar. Mean number of perforations were significantly more in group A. Occlusion stability was 69.2% in group A and 84.6% in group B. The mean value of plaque index in group A was 2.85±0.25 and in group B was 1.15± 0.16. Conclusion: In conclusion, plaque deposition was more in group A. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):175-180